2009
DOI: 10.1016/j.foodchem.2009.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons (PAHs) in sugarcane juice

Abstract: a b s t r a c tSugarcane juice is a common beverage in many Brazilian cities. At harvesting season most sugarcane plantation is burnt and this procedure has been shown as an important source of PAHs emission. In the present study 80 samples of sugarcane juice collected from two Brazilian cities, in two different periods, were analysed for the presence of four PAHs: benz(a)anthracene, benzo(b)fluoranthene, benzo(k)fluoranthene and benzo(a)pyrene. PAHs were detected in 50% of the samples. The samples collected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 14 publications
0
17
0
5
Order By: Relevance
“…The analytical procedures mostly used for PAHs involve several steps with an extensive clean-up and require large volumes of organic solvents. 2,11,18,[21][22][23] Solid-phase extraction (SPE) has been successfully applied, showing good selectivity and recovery, requiring smaller amounts of solvent for elution and resulting in shorter time analysis. [23][24][25] Although several methods for different sets of PAHs have been described in the literature, no one has designed for a simultaneous HPLC determination of the 13 PAHs, considered genotoxic and carcinogenic by the JECFA, in edible oils.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analytical procedures mostly used for PAHs involve several steps with an extensive clean-up and require large volumes of organic solvents. 2,11,18,[21][22][23] Solid-phase extraction (SPE) has been successfully applied, showing good selectivity and recovery, requiring smaller amounts of solvent for elution and resulting in shorter time analysis. [23][24][25] Although several methods for different sets of PAHs have been described in the literature, no one has designed for a simultaneous HPLC determination of the 13 PAHs, considered genotoxic and carcinogenic by the JECFA, in edible oils.…”
Section: Introductionmentioning
confidence: 99%
“…1 Thus, variable levels of PAHs have been reported in different food categories and beverages including vegetables and fruits, cereals, oils and fats, smoked products, coffee and tea. [2][3][4][5][6][7][8][9][10][11][12] PAHs were evaluated by the International Programme on Chemical Safety (IPCS), the Scientific Committee on Food (SCF) and by the Joint FAO/WHO Expert Committee on Food Additives (JECFA). SCF concluded that 15 Vol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPA são compostos de baixa hidrossolubilidade, mostrando-se geralmente muito lipossolúveis; são produzidos por combustão incompleta ou pirólise de matéria orgânica (HOWARD; FAZIO, 1980;DANYI et al, 2009;TFOUNI et al, 2009). Sua síntese é influenciada pelos seguintes fatores: tipo de biomassa presente, pressão, quantidade de oxigênio disponível e, principalmente, de calor (CONDE et al, 2004).…”
Section: Aspectos Gerais Da Formação Dos Hpaunclassified
“…Foram coletadas amostras de caldo de cana nos municípios paulistas de Ribeirão Preto e Campinas, buscando determinar a concentração de benzo(a)antraceno, benzo(b) fluorantreno, benzo(k)fluorantreno e benzo(a)pireno, além da influência do processo de queima da cana no nível destes constituintes (TFOUNI et al, 2009). As amostras coletadas na época em que a cana é queimada mostraram resultados quatro vezes maiores do que as coletadas na entressafra, apontando a queima da cana com uma importante fonte de contaminação.…”
Section: Alimentos Com Alto Teor De Carboidratosunclassified